Respuesta :
Answer:
2FeBr₃ + 3Na₂S → Fe₂S₃ + 6NaBr
Explanation:
The expression to be balanced is given as:
FeBr₃ + Na₂S → Fe₂S₃ + NaBr
To balanced this chemical equation, we can use a simple mathematical approach.
Simply use the alphabets a, b, c and d to represent the numbers that will make the equation balanced;
aFeBr₃ + bNa₂S → cFe₂S₃ + dNaBr
Conserving Fe;
a = 2c
Conserving Br;
3a = d
Conserving Na;
2b = d
Conserving S;
b = 3c
Let a = 1, b = [tex]\frac{3}{2}[/tex]
c = [tex]\frac{1}{2}[/tex] d = 3
Multiply through by 2 to get whole number ratios;
a = 2, b = 3 , c = 1 and d = 6
2FeBr₃ + 3Na₂S → Fe₂S₃ + 6NaBr